Efficiency of the generalized restricted difference-based almost unbiased ridge estimator in partially linear model. Issue 5 (4th March 2022) - Wu, Jibo
Abstract: In this paper, the generalized restricted difference-based almost unbiased ridge estimator in partially linear model is presented, when it is supposed that the regression parameters may be restricted to a subspace and compare the proposed estimators in the sense of the quadratic bias and scalar mean squared error criteria. Finally, a simulation study is given to explain the performances of the estimators.